Islamic Business Ethics in Gourami Farming: A Strategic Perspective - Andhika Pradana; Wanda Putri Ramadhani (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
This study aims to evaluate whether the business strategies implemented by gourami farmers in Sunyalangu Village, Banyumas Regency, align with Islamic business ethics. The research employs a qualitative descriptive approach, utilizing data gathered from interviews, observations, and documentation. Data analysis involves processes such as data reduction, data presentation, and drawing conclusions. The findings indicate that gourami farmers in Sunyalangu Village adhere to Islamic business ethics by practicing honesty, maintaining a friendly demeanor, safeguarding consumer rights, and refraining from disparaging competitors' businesses.